Visual Correlates of Fitness to Drive in Adults With Multiple Sclerosis. (January 2018) - Classen, Sherrilene; Krasniuk, Sarah; Morrow, Sarah A.; Alvarez, Liliana; Monahan, Miriam; Danter, Tim; Rosehart, Heather
The impact of visual and visual-cognitive impairments on fitness to drive in persons with multiple sclerosis (PwMS) are not well studied. We quantified visual correlates of fitness to drive in 30 PwMS. PwMS completed visual ability and visual attention assessments, and a standardized on-road assessment, and were compared with 145 older volunteer drivers. PwMS (vs. older volunteer drivers) made more total ( W = 12, 139, p = .03) and critical driving errors (predictive of crashes) in adjustment to stimuli ( W = 11, 352, p < .0001), vehicle positioning ( W = 11, 449, p < .0001), and wide lane turns ( W = 9, 932, p < .0001). PwMS who failed (vs. passed) made more total ( W = 325, p = .04), adjustment to stimuli ( W = 321.5, p = .02), and gap acceptance errors ( W = 333, p = .03). For PwMS, adjustment to stimuli errors moderately correlated with visual acuity (ρ = .50, p = .006), and gap acceptance errors moderately correlated with visual processing speed (ρ = .40, p = .03). Visual-cognitive impairments may be indicative of critical driving errors and help identify PwMS at-risk for fitness to drive.